The tiger and the terrorist: how Malaysian NGOs deal with terrorism - Ahmad H.Osman, Rahmah; Mekki, Abdullah (IIUM Press, International Islamic University Malaysia, 2017)
This paper investigates the efforts of Malaysian NGOs in spreading peace and stopping terrorism. Instead of taking the usual sociological approach, this article will take a cultural-critical approach, drawing on the theories of Western and Muslim intellectuals in order to gain greater insight into the peace-promoting efforts. This article will look into four Malaysian NGOs: PERKIM, YADIM, ABIM, and JIM. These NGOs are representative of Malaysian NGOs as a whole, with regards to their efforts in defusing terrorism. The first section of this article provides a justification for the use of a cultural-critical approach. The second section looks at the space open for NGOs to work in, and examines the importance of providing counter-narratives to terrorist rhetoric. The third section looks at the unique narrative on Islam in Malaysia, and how that helps NGOs in peace-building efforts. The fourth section examines the social projects NGOs provide and sees how they target the roots of terrorism. The fifth section relates some of the challenges Malaysian NGOs face in their peace-building efforts. This article concludes that prevalent strategies in Terrorism Studies need to be re-examined and re-evaluated in order to make them more effective. It is hoped this article will give a new perspective on counter-terrorism strategies and help policy makers in better understanding the ubiquitous threat terrorists pose.